Pengaruh Leverage, Pertumbuhan Penjualan dan Ukuran Perusahaan Terhadap Profitabilitas - Putra, A.A. Wela Yulia; Badjra, Ida Bagus (E-Jurnal Manajemen; Vol 4 No 7 (2015), 2015)
Companies with good performance will be able to achieve the goals to be achieved by the company, which is to maximize the value of the company. That goals can be achieved by increasing the profitability of the company. The purpose of this study was to determine the significance of the effect of leverage, sales growth and firm size to profitability. This research was conducted at the Food and Beverage Industry company in Indonesia Stock Exchange with a sample of 12 companies that obtained through purposive sampling method. The resulted of the study with multiple linear analysis found that leverage had a significant negative effect on profitability, while sales growth and firm size had no significant negative effect on profitability.
Keywords: leverage, sales growth, size, profitability